Kajian Konsep Kawasan Ramah Lansia Perkotaan - Indriani Suroto, Fitri; Rini, Erma Fitria; Rahayu, Murtanti Jani (LPPM Universitas Terbuka, 2024)
The elderly population is projected to grow rapidly in the coming years, particularly in developing countries such as Indonesia. So, this means that the need for areas that are friendly for the elderly must be fulfilled to support the formation of healthy and independent elderly people. Elderly-friendly areas are also needed to create an inclusive environment without sacrificing the rights of other groups. The diverse needs of the elderly mean that an area must be adapted to the limitations of the elderly so that it can accommodate them. Knowing the suitability of an area for the elderly-friendly concept is important for realizing the Age Friendly City (AFC) concept. Therefore, this research aims to determine the suitability of an area for the elderly-friendly concept using a scoring method for elderly-friendly components. Data was obtained through field observations, questionnaires, and relevant literature studies. Based on the results of the scoring analysis of 6 elderly-friendly variables, there are 5 variables whose indicators perfectly match the elderly-friendly components. The research results also show that the research area is suitable for the elderly-friendly concept.